2001
DOI: 10.1103/physrevlett.88.024502
|View full text |Cite
|
Sign up to set email alerts
|

Noise Induced Bistability of Parametric Surface Waves

Abstract: We report an experimental study on the effect of an external multiplicative noise on a subcritical bifurcation leading to the parametric amplification of surface waves. We show that the probability density function of the wave amplitude in the presence of noise has two maxima that do not correspond to any of the deterministic states. When the deterministic forcing is varied in the presence of noise, these most probable values give two new branches in the bifurcation diagram that involve a much larger differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 19 publications
0
28
0
Order By: Relevance
“…While there are observations of noise-induced bistabilities in other physical and engineering systems (27,28), there is little such conclusive experimental evidence in biomolecular structures to date, although it might be difficult to deconvolve the hereinpredicted effects from the measurement noise. Furthermore, single-cell measurements of protein activity and gene expression are (although increasing) few, and of those, fewer still follow single-cell expression temporally at sufficient resolution.…”
Section: Discussionmentioning
confidence: 99%
“…While there are observations of noise-induced bistabilities in other physical and engineering systems (27,28), there is little such conclusive experimental evidence in biomolecular structures to date, although it might be difficult to deconvolve the hereinpredicted effects from the measurement noise. Furthermore, single-cell measurements of protein activity and gene expression are (although increasing) few, and of those, fewer still follow single-cell expression temporally at sufficient resolution.…”
Section: Discussionmentioning
confidence: 99%
“…In order to destroy the narrow band time response of the waves, we have repeated our experiments using parametric excitation with Gaussian noise in the frequency band f 0 ͓30, 50͔ Hz. Noise driven parametric surface waves have been studied by Residori et al 27 In our case, noise gives rise to an intermittent temporal global surface response: the surface randomly alternates between episodes with turbulent waves and the flat state. We have found that with parametric excitation by noise, only the first three peaks in the frequency spectrum are discernible, but all our conclusions regarding the spectral exponents remained unaltered.…”
Section: -5mentioning
confidence: 99%
“…Only recently, experiments on the effect of noise on parametrically driven surface waves have been performed in the case of a subcritical bifurcation. New phenomena, such as noise-induced-bistability, have been reported [11].…”
Section: Introductionmentioning
confidence: 99%